2021
DOI: 10.1155/2021/9942090
|View full text |Cite
|
Sign up to set email alerts
|

Antiaging Effects of Vicatia thibetica de Boiss Root Extract on Caenorhabditis elegans and Doxorubicin‐Induced Premature Aging in Adult Mice

Abstract: The roots of Vicatia thibetica de Boiss are a kind of Chinese herb with homology of medicine and food. This is the first report showing the property of the extract of Vicatia thibetica de Boiss roots (HLB01) to extend the lifespan as well as promote the healthy parameters in Caenorhabditis elegans (C. elegans). For doxorubicin- (Doxo-) induced premature aging in adult mice, HLB01 counteracted the senescence-associated biomarkers, including P21 and γH2AX. Interestingly, HLB01 promoted the expression of collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The approval number was 20211009013. Mouse assays were conducted according to the previously reported procedures [ 12 , 17 ]. Metformin served as a positive control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The approval number was 20211009013. Mouse assays were conducted according to the previously reported procedures [ 12 , 17 ]. Metformin served as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Thrashing Assay and Pharyngeal Pumping Assay. The thrashing assay and pharyngeal pumping assay were performed following the previously described methods [12]. The experiments were performed with reference to the lifespan assay.…”
Section: Caenorhabditis Elegans Maintenance and Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported that plant extracts or natural phytochemicals improve the lifespan of worms and mammals. 4,28 To examine the effect of GE on the lifespan of C. elegans, the worms were treated with different concentrations of GE. As shown in (Fig.…”
Section: Ge Rendered Longevity To C Elegansmentioning
confidence: 99%